Implementasi Arduino Atmega pada Pompa Air Automatik Perahu Nelayan Gili Marinkik Lombok Timur - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Marzuki Adami; Abdul Gofur (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
Maringkik is a small island located in the south of the island of Lombok which is included in the territorial area of East Lombok Regency, West Nusa Tenggara. Gili Meringkik fishermen are active in catching fish using boats whose raw materials are made of wood which is prone to leakage. In the condition of a leak, the fishermen pump water into their boats or experience manual leakage continuously. Based on these problems, an automatic device is needed as a water pump in fishing boats to increase the amount of production. The device is a water pump on a boat using an Arduino microcontroller-based Ultrasonic Sensor. The research was conducted to build a water pump that enters the fishing boat automatically. The working system of this tool is if any water enters the bottom floor of the ship with the ultrasonic sensor water level when it detects the water level is, and the water pump will be active to immediately suck the water out of the ship so that the ship does not sink. This tool can help fishermen with removing the water that enters the boat. In addition, so that fishermen can easily control the boat from afar, this tool is able to discharge water on fishing boats automatically when the water level has exceeded the height limit, which interferes with sailing.